The Influence of Principal Leadership and Work Motivation on Kindergarten Teacher Discipline - Rahayu, Sri; Yuliejatiningsih, Yovita; Maryanto (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study analyzes the influence of principal leadership and work motivation on kindergarten teacher discipline in Temanggung District. Teacher discipline plays a crucial role in maintaining a conducive and high-quality learning environment. Effective principal leadership and strong work motivation are essential factors in fostering teacher discipline, ensuring professionalism, and improving educational outcomes. This research employs a quantitative approach using a survey method. The study sample consists of 106 kindergarten teachers selected through proportional random sampling. Data were collected using a validated and reliable questionnaire, then analyzed using simple and multiple regression techniques. The findings reveal that principal leadership significantly influences teacher discipline, with a t-value of 5.923 and a contribution of 43.3%. Work motivation also has a significant effect, with a t-value of 3.241 and a contribution of 36.2%. Simultaneously, these two factors contribute 59.8% to teacher discipline. These results emphasize the importance of strengthening principal leadership and implementing strategies to enhance teacher motivation. Schools should focus on leadership training programs and motivation-enhancing initiatives to create a more disciplined and professional educational environment.